2020
DOI: 10.3390/ijerph17218196
|View full text |Cite
|
Sign up to set email alerts
|

Are Vulnerable Communities Thoroughly Informed on Mosquito Bio-Ecology and Burden?

Abstract: Mosquitoes account for a significant burden of morbidity and mortality globally. Despite evidence of (1) imminent anthropogenic climate and environmental changes, (2) vector-pathogen spatio-temporal dynamics and (3) emerging and re-emerging mosquito borne infections, public knowledge on mosquito bio-ecology remain scant. In particular, knowledge, attitude and practices (KAPs) on mosquitoes are often neglected despite otherwise expensive remedial efforts against consequent infections and other indirect effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Thus, local flies (e.g., stable, horse, house and blow flies) may be important arthropod vectors of medical and veterinary importance in triggering and exacerbating secondary infections directly or indirectly. Although mosquito abundance and refugia hotspots may be influenced by climatic and anthropogenic activities (e.g., degraded habitats) [ 69 , 88 , 89 ], this study further reported that pit latrines and food wastes were likely the major attractants to cockroaches and flies in homesteads. Therefore, it remains essential to assess the pathogenicity of urban pests across rural-urban landscapes.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, local flies (e.g., stable, horse, house and blow flies) may be important arthropod vectors of medical and veterinary importance in triggering and exacerbating secondary infections directly or indirectly. Although mosquito abundance and refugia hotspots may be influenced by climatic and anthropogenic activities (e.g., degraded habitats) [ 69 , 88 , 89 ], this study further reported that pit latrines and food wastes were likely the major attractants to cockroaches and flies in homesteads. Therefore, it remains essential to assess the pathogenicity of urban pests across rural-urban landscapes.…”
Section: Discussionmentioning
confidence: 72%
“…Knowledge, here, referred to what residents knew about arthropod vector biology, ecology, taxonomy and control practices. The dependent variables (knowledge items) were evaluated against the independent factors (e.g., district, age, gender and educational background) to quantify the responses using rating, nominal and ordinal scales following modifications from Buxton et al [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the random distribution assumption, the prevalence of each disease condition was obtained from the individual study estimate (ES), which includes a standard error (seES) and lower and upper confidence intervals. The pooled estimates were calculated and reported with respect to the relative weight given for each study [90,91]. Egger's regression test analyses were used to check the publication bias [92].…”
Section: Discussionmentioning
confidence: 99%